Political alternation at sub-national democracies : the cases of the Azores, Madeira and the Canary Islands - Martins, Teresa Maria Ruel, 1981- (2015)
Tese de doutoramento, Ciência Política (Política Comparada), Universidade de Lisboa, Faculdade de Direito, Universidade de Lisboa, Faculdade de Letras, Universidade de Lisboa, Instituto de Ciências Sociais, 2015